Clinical impact of first-line therapeutic strategies in BRAF V600E-mutant metastatic colorectal cancer: real-world evidence and prognostic insight - Yeh, Chia-Chang; Chiang, Shih-Wei; Chiang, Feng-Fan (Frontiers in Oncology, 2025)
BackgroundBRAF V600E-mutant metastatic colorectal cancer (mCRC) is associated with poor prognosis and limited response to standard therapies. Recent clinical trials have explored the benefit of targeted therapies, but real-world data remain limited.MethodsThis retrospective study analyzed 36 patients with BRAF V600E-mutant mCRC who received first-line treatment between 2018 and 2024 at Taichung Veterans General Hospital. Patients were grouped by initial regimen: chemotherapy alone, chemotherapy plus anti-VEGF (bevacizumab), or chemotherapy combined with BRAF-targeted ± MEK inhibitors. Primary endpoints were overall survival (OS) and progression-free survival (PFS); secondary endpoints included objective response rate (ORR) and disease control rate (DCR).ResultsMean OS and PFS were longest in patients receiving chemotherapy plus anti-VEGF (21.2 and 10.5 months, respectively), compared to chemotherapy alone (OS 14 months, PFS 7.7 months) and anti-BRAF targeted therapy (OS 13.5 months, PFS 6.5 months). The highest ORR (53.8%) and DCR (76.9%) were observed in patients receiving BRAF-targeted regimens. Multivariate analysis identified liver metastasis and ECOG ≥2 as poor prognostic factors. Unexpectedly, right-sided tumors were associated with improved survival (HR: 0.20, p = 0.028). Subsequent use of BRAF-targeted therapy in some patients may have contributed to extended OS.ConclusionsIn this real-world cohort, chemotherapy combined with anti-VEGF provided the best survival outcomes, while BRAF-targeted strategies showed promising response rates. Liver involvement and poor performance status remained negative prognostic indicators. These findings support a personalized treatment approach and highlight the need for continued prospective validation.